Socioeconomic Disparities in Adherence and Outcomes After Heart Transplant: A UNOS (United Network for Organ Sharing) Registry Analysis. (March 2018) - Wayda, Brian; Clemons, Autumn; Givens, Raymond C.; Takeda, Koji; Takayama, Hiroo; Latif, Farhana; Restaino, Susan; Naka, Yoshifumi; Farr, Maryjane A.; Colombo, Paolo C.; Topkara, Veli K.
Abstract : Background: There is mixed evidence of racial and socioeconomic disparities in heart transplant outcomes. Their underlying cause—and whether individual- or community-level traits are most influential—remains unclear. The current study aimed to characterize socioeconomic disparities in outcomes and identify time trends and mediators of these disparities. Methods and Results: We used United Network for Organ Sharing registry data and included 33 893 adult heart transplant recipients between 1994 and 2014. Socioeconomic status (SES) indicators included insurance, education, and neighborhood SES measured using a composite index. Black race and multiple indicators of low SES were associated with the primary outcome of death or retransplant, independent of baseline clinical characteristics. Blacks had lower HLA and race matching, but further adjustment for these and other graft characteristics only slightly attenuated the association with black race (HR, 1.25 after adjustment). This and the associations with neighborhood SES (HR, 1.19 for lowest versus highest decile), Medicare (HR, 1.17), Medicaid (HR, 1.29), and college education (HR, 0.90) remained significant after full adjustment. When comparing early (1994–2000) and late (2001–2014) cohorts, the disparities associated with the middle (second and third) quartiles significantly decreased over time, but those associated with lowest SES quartile and black race persisted. Low neighborhood SES was also associated with higher risks of noncompliance (HR, 1.76), rejection (HR, 1.28), hospitalization (HR, 1.13), and infection (HR, 1.10). Conclusions: Racial and socioeconomic disparities exist in heart transplant outcomes, but the latter may be narrowing over time. These disparities are not explained by differences in clinical or graft characteristics. Abstract : Supplemental Digital Content is available in the text.